Delivery of siRNA Therapeutics: Barriers and Carriers - Wang, Jie (Springer US, 2010)
RNA interference is a naturally occurring endogenous regulatory process where short double-stranded RNA causes sequence-specific posttranscriptional gene silencing. Small interference RNA (siRNA) represents a promising therapeutic strategy. Clinical evaluations of siRNA therapeutics in locoregional treatment settings began in 2004. Systemic siRNA therapy is hampered by the barriers for siRNA to reach their intended targets in the cytoplasm and to exert their gene silencing activity. The three goals of this review were to provide an overview of (a) the barriers to siRNA delivery, from the perspectives of physicochemical properties of siRNA, pharmacokinetics and biodistribution, and intracellular trafficking; (b) the non-viral siRNA carriers including cell-penetrating peptides, polymers, dendrimers, siRNA bioconjugates, and lipid-based siRNA carriers; and (c) the current status of the clinical trials of siRNA therapeutics.